Intersecting religion and ethnicity: Drawing boundaries in talk-in-interaction. Issue 2 (1st December 2021) - KLESSMANN, MARIA
Abstract : People of Romani background are usually labelled as members of an "ethnic minority" and identified along dominantly ethnicized notions and markers. Discursively, this neglects individuals' different self-perceptions and multiple belongings. This contribution looks at interactional data and material from workshops conducted in Germany as part of the EU-wide initiative RoMed (Mediation for Roma). The initiative aimed to strengthen opportunities for local participation by people of Romani background in various European cities and communities between 2011–2017. A conversation analytical approach (e.g. at practices of categorization) is used to examine excerpts from group discussions ahead of a meeting with public officials. From an intersectional perspective I look at how boundaries are drawn, blurred, or destabilized between issues of religiosity and ethnicity. The article discusses boundary-drawing as a symbolic ordering process, highlighting the hegemonic discourses which are reproduced and challenged in the investigated linguistic material. The boundaries drawn and negotiated show the delicate balance between the staging of ethnic and religious affiliations and concerns and their political mobilization.